Modelling of Continuum Damage for Application Elasto-Viscoplastic Bodner-Partom Constitutive Equations - AMBROZIAK, A. (Engineering Transactions, 2007)
The aim of the paper is to propose an application of the continuum damage model proposed by Lemaitre to the elasto-viscoplastic constitutive equations of the Bodner–Partom model. The proposed approach has been implemented into subroutines of the FE code MSC.Marc as the user’s viscoplastic subroutine UVSCPL and has been used to perform the FE numerical simulations. Comparison is given of the following two variants: 1) uniaxial creep test results for a nickel-based B1900+Hf superalloy at high temperatures and 2) calculation based on the constitutive equations with the inclusion of isotropic damage models.